Ocular complications of diabetes mellitus in a pediatric population and proposals for screening and follow-up programs. - Diplotti, Laura; Pignatto, Silvia; Franco, Francesca; Zanatta, Manuela; Veritti, Daniele; Cogo, Paola; Lanzetta, Paolo (Therapeutic Advances in Ophthalmology, 2023)
Background: Diabetes mellitus (DM) is one of the world's greatest health emergencies of the 21st century. Ocular complications of DM are commonly chronic and progressive, but vision loss can be effectively prevented or delayed with early detection and timely treatment. Therefore, regular comprehensive ophthalmologic examinations are mandatory. Ophthalmic screening and dedicated follow-up for adults with DM are well established, whereas, there is no consensus on optimal recommendations for the pediatric population, reflecting the lack of clarity about the current burden of disease in this age group. Objectives: To determine the epidemiology of ocular complications of diabetes and to assess optical coherence tomography (OCT) and optical coherence tomography angiography (OCTA) macular features in a pediatric population with DM. To review ophthalmological screening and follow-up plans for the diabetic pediatric population. Design: Observational study. Methods: Retrospective consecutive cohort study of all 165 diabetic patients (330 eyes) aged 0–18 years, examined between January 2006 and September 2018 at the Pediatric Department of 'S. Maria della Misericordia' Udine Hospital who underwent at least one complete ophthalmologic examination at the Ophthalmology University Clinic at the Udine Hospital. OCT and OCTA data were available for 37 patients (72 eyes, 2 excluded). The associations between ocular complications and selected potential risk factors were evaluated by univariate analyses. Results: No patient had signs of ocular diabetic complications or any macular morphological or micro-vascular impairment, regardless of any potential risk factor. The prevalence of strabismus and refractive errors in the study group, was found to be similar to non-diabetic pediatric populations. Conclusion: Screening and follow-up of ocular diabetic complications in children and adolescents could be performed less frequently than in adults with diabetes. There is no need to screen potentially treatable visual disorders in diabetic children earlier or more frequently than in the healthy children thus reducing time spent in hospital and permitting a better tolerance to medical examinations in diabetic pediatric patients. We described the OCT and OCTA patterns in a pediatric population with DM.